The Role of Teacher’s Professional Attitude on Mediating the Effect of Good Public Governance and School Climate to Economic Teacher’s Performance of SHS/Islamic SHS - Lestari, Maharesi Dewi; Widodo, Joko; Khafid, Muhammad (Universitas Negeri Semarang, 2018)
The purpose of this research is to analyze how the role of teacher’s professional attitude on mediating the effect of GPG principles implementation and school climate on economic teacher’s performance of SHS/Islamic SHS in Purbalingga Regency. The approach that used on this research is a quantitative approach with survey method. The population in this research are all of senior high school / islamic senior high school economic teachers in Purbalingga District, on amount 30 teachers with 30 sample. Data collection was carried out by questionnaire. Data analysis was carried out with descriptive analysis and Structural Equation Modeling (SEM) based on variance by using SmartPLS version 2.0.m3 software. The results of this research showed that: (1) the direct effect on the economic teacher’s performance is only influenced by school climate with contribution value of 57.2%; (2) the direct effect on the teacher's professional attitude is only influenced by GPG principles implementation with contribution value of 84.8%; (3) the teacher's professional attitude is not proven mediating the influence of GPG principles implementation and school climate on economic teacher’s performance.